Priesthood and Community: the Social and Economic Background of the Parochial Clergy in the diocese of Worcester to 1348. (2nd January 2017) - Robinson, David
Abstract : The present study uses the ordination lists in the Worcester episcopal registers to identify almost 3, 000 clergy and, using the 1327 lay subsidy, to establish the probable wealth of their families. The strengths and weaknesses of the evidence and of the nominal linkages are assessed and the diocese of Ely is used for comparison. Evidence from the Hundred Rolls for Brailes in Warwickshire and other sources are used to discover the landholdings of individual ordinands' families. Ordinands were required to be free, by birth or manumission, and the White Book of Worcester cathedral priory reveals the extent to which men on the priory estates who were manumitted then sought ordination. Inquisitions post mortem are used to show that places in eastern Gloucestershire produced greater numbers of ordinands than places in south-western Gloucestershire regardless of whether free or servile tenure predominated.